2020
DOI: 10.1007/s00127-020-01961-2
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of social network size in the temporal association between formal social participation and mental health: a longitudinal analysis using two consecutive waves of the Survey of Health, Ageing and Retirement in Europe (SHARE)

Abstract: Introduction Previous studies have shown that engaging in formal social participation may protect against declining mental health, but social network size (the number of close social ties a person has) may moderate the relationship. We assessed the potential moderating role of social network size using longitudinal data. Methods Nationally representative data from two consecutive waves (2011, 2013) of the SHARE survey were analyzed. The data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…Female baboons that have more grooming partners (i.e., allies) experience less harassment (Dunbar, 2018a), and have lower cortisol titres (Crockford et al, 2008;Wittig et al, 2008), higher wound healing (Archie et al, 2014) and lower infection rates (Balasubramaniam et al, 2016) and live longer (Silk et al, 2003(Silk et al, , 2009(Silk et al, , 2010Cheney et al, 2016), and in addition produce more offspring that in turn have higher survival rates. Similar results have been reported for chimpanzees (Wittig et al, 2016), macaques (Young et al, 2014;McCowan et al, 2016;Brent et al, 2017), feral horses (Cameron et al, 2009;Nuñez et al, 2015) and dolphins (Frère et al, 2010), as well as humans (for whom there is a substantial epidemiological literature demonstrating very significant effects of the number of close friends on both psychological and physical health and wellbeing, as well as longevity: Holt-Lunstad et al, 2010;Dunbar, 2018b;Santini et al, 2020).…”
Section: Managing Fertility Declinesupporting
confidence: 78%
“…Female baboons that have more grooming partners (i.e., allies) experience less harassment (Dunbar, 2018a), and have lower cortisol titres (Crockford et al, 2008;Wittig et al, 2008), higher wound healing (Archie et al, 2014) and lower infection rates (Balasubramaniam et al, 2016) and live longer (Silk et al, 2003(Silk et al, , 2009(Silk et al, , 2010Cheney et al, 2016), and in addition produce more offspring that in turn have higher survival rates. Similar results have been reported for chimpanzees (Wittig et al, 2016), macaques (Young et al, 2014;McCowan et al, 2016;Brent et al, 2017), feral horses (Cameron et al, 2009;Nuñez et al, 2015) and dolphins (Frère et al, 2010), as well as humans (for whom there is a substantial epidemiological literature demonstrating very significant effects of the number of close friends on both psychological and physical health and wellbeing, as well as longevity: Holt-Lunstad et al, 2010;Dunbar, 2018b;Santini et al, 2020).…”
Section: Managing Fertility Declinesupporting
confidence: 78%
“…Results from the present study indicated that low involvement in organized activities was associated with increased odds of mental distress, both among men and women. These findings are supported by results from prospective studies among European adults suggesting that involvement in social organized activities predicted higher quality of life and lower level of depressive symptoms over time and be a protective factor against the onset or development of chronic conditions, especially among individuals with few close social ties [16,46]. Finally, a Norwegian population-based study has suggested a dose-response effect of participation in organized activities on perceived health, anxiety, depression, and satisfaction with life in both women and men, and that men who engaged specifically in receptive, rather than creative, cultural activities reported better healthrelated outcomes [47].…”
Section: Discussionsupporting
confidence: 54%
“…There were 18,398 respondents who exclusively answered the SHARE Corona survey through telephone interview after the outbreak of the pandemic but could not be successfully approached in person before the suspension of the Wave 8 fieldwork. These data have been carefully augmented with information from previous waves where appropriate ( 45 52 ). The SHARE data are unanimous based on full probability samples ( 53 , 54 ), providing internationally comparable data that can add important insights to recent studies, which are frequently restricted to the national level.…”
Section: Methodsmentioning
confidence: 99%